Extraction of anthocyanins from Clitoria ternatea L. petals in Vietnam and determination of its antioxidant and antimicrobial activities - Ha, Vy T.N.; Le , Ngoc T.H. (Jordan Journal of Pharmaceutical Sciences, 2022)
In this study, the effects of various factors on anthocyanins extracted from ClitoriaTernatea L. petals were determined. In addition, phytochemical properties, antioxidant ability, antimicrobial capacity, and application of anthocyanins extractions were also investigated. As a result, the highest proportion of anthocyanin, 1.21 mg/g fresh weight (FW), was obtained when extracting ClitoriaTernatea L. petals with 100% methanol, with the solvent/sampleratio of 10ml/g at 37oC for an hour. The highest total phenolic content (TPC) was 24.7x103±8.55x102 µg gallic acid equivalent (GAE)/g FW, while the figures for total flavonoid content was 18.8±0.149 mg quercetin equivalent (QE)/g FW. The values for 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity and the highest total antioxidant activity were EC50=904.1µg/ml and 2.86x103±1.01x101 µg ascorbic acid equivalent (AAE)/g FW, respectively. The inhibitions to Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa were shown with the minimum inhibitory concentration (MIC) of 90 mg/ml and 180 mg/ml. It also showed that the ClitoriaTernatea L. petal extract also had the potential to be developed into a pH indicator, however, further study should be carried out to obtain a highly qualified one.